An Empirical Study of an Auction with Asymmetric Information - Porter, Robert H.; Hendricks, Kenneth (American Economic Review, 1988)
This paper examines federal auctions for drain age leases on the Outer Continental Shelf from 1959 to 1969. These are leases that are adjacent to tracts on which a deposit has been discovered. The authors find that the data strongly support the hypotheses that neighbor firms are better informed about the value of a lease than nonneighbor firms; that neighbor firms coordinate their bidding decisions; and that both types of firms bid strategically in accordance with the Bayesian-Nash equilibrium model for first-price, sealed-bid auctions with asymmetric information.